Stem Cells Injected into the Deaf Rat Cochlea via Round Window Could Survive for at Least One Week in the Endolymph - Niknazar, Somayeh; Abbaszadeh, Hojjat-Allah; Peyvandi, Ali Asghar (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Noise-induced hearing loss (NIHL) is caused by chronic exposure to high-intensity sound. Although noise hazard has been extensively studied in the past decades, cochlear implants and hearing aids are only safe and clinically effective intervention in hearing-impaired person. In recent years, stem cell therapy has been studied to repair damaged inner ear tissue including hair cells and spiral ganglion neurons (SGNs). Because of small size and complex structure of the cochlea, it is difficult to transplant stem cells. It is necessary; stem cell injection procedure has a minimal adverse effect on target tissue. Cochleostomy are currently used to inject stem cells that can impair hearing. In addition, cell viability is an essential factor in the regeneration of damaged hair cells. Aim: The aim of this study was to examine the survival of bone marrow mesenchymal stem cells (BMSCs) injected through the round window of the NIHL rat model. Methods: Adult male rats were exposed to the 110 dB white noise paradigm for 6 hours in 5 days to induce deafness. Distortion-product otoacoustic emission (DPOAE) was recorded before and after noise exposure. Hoechst labeled-cells were transplanted into the rat cochlea through the round window. Hoechst- labelled MSCs were assayed in the endolymph for 24h, 72h, seven and 10 days after injection. Results: Our findings revealed that stem cell transplantation into the cochlea via round window niche is a safe surgical approach. As well, cells transplanted into the endolymph survived for a postoperative period of at least 1 week. Conclusion: BMSC can survive at least one week in adult rat cochlea after injection through the round window niche.